Exploring the efficacy of tumor electric field therapy against glioblastoma: An in vivo and in vitro study. (28th October 2021) - Wu, Hao; Yang, Lin; Liu, Hanjie; Zhou, Dan; Chen, Dikang; Zheng, Xiaoque; Yang, Hui; Li, Chong; Chang, Jiusheng; Wu, Anhua; Wang, Zhifei; Ren, Nianjun; et al.
Abstract: Aims: Tumor electric fields therapy (TTFields) is emerging as a novel anti‐cancer physiotherapy. Despite recent breakthroughs of TTFields in glioma treatment, the average survival time for glioblastoma patients with TTFields is <2 years, even when used in conjugation with traditional anti‐cancer therapies. To optimize TTFields‐afforded efficacy against glioblastoma, we investigated the cancer cell‐killing effects of various TTFields paradigms using in vitro and in vivo models of glioblastoma. Methods: For in vitro studies, the U251 glioma cell line or primary cell cultures prepared from 20 glioblastoma patients were treated with the tumor electric field treatment (TEFT) system. Cell number, volume, and proliferation were measured after TEFT at different frequencies (100, 150, 180, 200, or 220 kHz), durations (24, 48, or 72 h), field strengths (1.0, 1.5, or 2.2V/cm), and output modes (fixed or random sequence output). A transwell system was used to evaluate the influence of TEFT on the invasiveness of primary glioblastoma cells. For in vivo studies, the therapeutic effect and safety profiles of random sequence electric field therapy in glioblastoma‐transplanted rats were assessed by calculating tumor size and survival time and evaluating peripheral immunobiological and blood parameters, respectively. Results: In the in vitro settings, TEFT was robustly effective in suppressing cell proliferation of both the U251 glioma cell line and primary glioblastoma cell cultures. The anti‐proliferation effects of TEFT were frequency‐ and "dose" (field strength and duration)‐dependent, and contingent on the field sequence output mode, with the random sequence mode (TEFT‐R) being more effective than the fixed sequence mode (TEFT‐F). Genetic tests were performed in 11 of 20 primary glioblastoma cultures, and 6 different genetic traits were identified them. However, TEFT exhibited comparable anti‐proliferation effects in all primary cultures regardless of their genetic traits. TEFT also inhibited the invasiveness of primary glioblastoma cells in transwell experiments. In the in vivo rat model of glioblastoma brain transplantation, treatment with TEFT‐F or TEFT‐R at frequency of 200 kHz and field strength of 2.2V/cm for 14 days significantly reduced tumor volume by 42.63% (TEFT‐F vs. control, p = 0.0002) and 63.60% (TEFT‐R vs. control, p < 0.0001), and prolonged animal survival time by 30.15% (TEFT‐F vs. control, p = 0.0415) and 69.85% (TEFT‐R vs. control, p = 0.0064), respectively. The tumor‐bearing rats appeared to be well tolerable to TEFT therapies, showing only moderate increases in blood levels of creatine and red blood cells. Adverse skin reactions were common for TEFT‐treated rats; however, skin reactions were curable by local treatment. Conclusion: Tumor electric field treatment at optimal frequency, strength, and output mode markedly inhibits the cell viability, proliferation, and invasiveness of primary glioblastoma cells in vitro independent of different genetic traits of the cells. Moreover, a random sequence electric field output confers considerable anti‐cancer effects against glioblastoma in vivo . Thus, TTFields are a promising physiotherapy for glioblastoma and warrants further investigation. Abstract : Primary tumor cells prepared from 20 patients were treated with the tumor electric field treatment system (TEFTS). The impact of genetic background on cell responses to TEFTS were evaluated. Cell volume, cell number and cell proliferation were measured after TEFT at different frequencies (100, 150, 180, 200, 220 kHz). A transwell system was used to evaluate the influence of TEFT on the invasiveness of primary cells. The therapeutic effect and safety of random sequence electric field therapy in tumor‐bearing rats were assessed by calculating tumor size and survival time and by evaluating other immunobiological and blood parameters. Twelve types of primary tumor cells with different genetic traits were all sensitive to electric field treatment. After sensitive frequency treatment, the volume of primary cells significantly increased compared to control group, while the proliferation and invasiveness of tumor cells were inhibited. The optimal frequencies among all 20 types of primary cells were divided into different categories: 30% of them had the optimal frequency of 180 kHz; 25% of them had the optimal frequency of 200 kHz; 15% of them had the optimal frequency of 150 kHz, and 30% of them had the optimal frequency of 220 kHz. Two cases were not sensitive to 200 kHz. The therapy with random sequence electric field output significantly reduced tumor size and elongated survival time of tumor‐bearing rats compared to the fixed sequence TEFT, while increased the incidence of dermatological side effects.